2021
DOI: 10.3390/ph14010066
|View full text |Cite
|
Sign up to set email alerts
|

In Situ-Forming Microparticles for Controlled Release of Rivastigmine: In Vitro Optimization and In Vivo Evaluation

Abstract: In this work, sucrose acetate isobutyrate (SAIB) and polylactic co-glycolic acid (PLGA) were used alone or in combination as a matrix-former (MF) to prepare long-acting injectable rivastigmine (RV) in situ-forming microparticles (ISM). RV-ISM were prepared by the emulsification of an internal phase, containing the drug and the matrix former(s), into an external oily phase containing a stabilizer. The statistical design, Central Composite Design (CCD), was adopted as a quality by design (QbD) approach to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The model was statistically validated using p-value, multiple correlation coefficient (R 2 ), adjusted multiple correlation coefficient (R 2 -adj), predicted multiple correlation coefficient (R 2 -pred) and adequate precision. Model selection was based on maximized R 2 -adj and R 2 -pred and a signal-to-noise ratio greater than 4 [ 33 , 34 ]. Three-dimensional response surface plots showing the effect of the CMAs on the different responses were created by Design-Expert ® software for graphical evaluation of the results and determination of the degree of interactions between the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…The model was statistically validated using p-value, multiple correlation coefficient (R 2 ), adjusted multiple correlation coefficient (R 2 -adj), predicted multiple correlation coefficient (R 2 -pred) and adequate precision. Model selection was based on maximized R 2 -adj and R 2 -pred and a signal-to-noise ratio greater than 4 [ 33 , 34 ]. Three-dimensional response surface plots showing the effect of the CMAs on the different responses were created by Design-Expert ® software for graphical evaluation of the results and determination of the degree of interactions between the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Haider et al ( 2021) developed in situ extended-release depots in the form of microparticles as a novel approach to improve the efficacy and tolerance of rivastigmine [95]. The polymeric microparticles were prepared using sucrose acetate isobutyrate (SAIB), PLGA, N-methyl-2-pyrrolidinone (NMP), and Pluronic ® F-68 by the emulsification method.…”
Section: Microformulationsmentioning
confidence: 99%
“…Furthermore, nor-LAAM (IC 50 =12 µM) is much less potent than LAAM (IC 50 =3 µM) and similar potency to methadone (IC 50 =10 µM) to inhibit human ether-a-go-go-related gene (hERG) channels associated with cardiac toxicity, indicating that nor-LAAM may represent an improved OUD treatment alternative to methadone and LAAM because of the wider therapeutic window [18]. Prior studies have shown that drug-loaded PLGA microparticles provide sustained drug release, easy parenteral administration, and are biocompatible/safe [19,20]. In the field of substance use disorder, PLGA polymers have been used and approved as marketed formulations like Vivitrol ® and Sublocade ® for alcohol and opioid dependence, respectively.…”
Section: Introductionmentioning
confidence: 99%